2019
DOI: 10.1038/s41467-019-09769-8
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial recognition of clustered RNA elements by the multidomain RNA-binding protein IMP3

Abstract: How multidomain RNA-binding proteins recognize their specific target sequences, based on a combinatorial code, represents a fundamental unsolved question and has not been studied systematically so far. Here we focus on a prototypical multidomain RNA-binding protein, IMP3 (also called IGF2BP3), which contains six RNA-binding domains (RBDs): four KH and two RRM domains. We establish an integrative systematic strategy, combining single-domain-resolved SELEX-seq, motif-spacing analyses, in vivo iCLIP, functional v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 67 publications
10
74
0
Order By: Relevance
“…These studies 15,16,40 of the IMP family as well as the data presented here show the necessity of the GG motif for all IMP family members. This provides an important consideration when performing next generation sequencing of IMP family targets.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These studies 15,16,40 of the IMP family as well as the data presented here show the necessity of the GG motif for all IMP family members. This provides an important consideration when performing next generation sequencing of IMP family targets.…”
Section: Discussionsupporting
confidence: 75%
“…Both CA and GG dinucleotides are necessary for binding to all the IMPs 15,16,40 , and were enriched by SELEX in this study. KH domains recognize 4–6 nt sequence elements 6 ; the IMP KH domains have been shown to recognize 4 nt sequences 15,16,40 , therefore the nucleotides flanking the CA and GG motifs are likely important for binding. Their selective enrichment also changed across the last three rounds of SELEX (i.e., rounds 7, 8 and 9) (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, IGF2BP3 binds to coding regions with a higher frequency than either IGF2BP1 or IGF2BP2 (Conway et al, 2016). In addition, a recent analysis of RNA recognition by multidomain IGF2BP proteins indicated that while IGF2BP1 associates with the CGGAC RNA motif, IGF2BP3 recognizes two related GGC-core elements (GGCA and CGGC), further supporting the existence of differences during the recognition of RNA (Schneider et al, 2019). The data described in the literature suggest that multiple RNA motifs, including CACA, UACA, AACA (Conway et al, 2016), GCAC (Palanichamy et al, 2016), and GGAC (Huang et al, 2018b), are recognized by the IGF2BP family, but the extent to which these sequences are specific to each RBP is still unclear.…”
Section: Specificities Of Igf2bp3 With Respect To the Other Igf2bpsmentioning
confidence: 94%